(untitled) (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2025)
Digital transformation has become a central agenda in public sector reform; however, empirical evidence from secondary cities in developing countries remains limited. This study examines the implementation of digital public service policies in Bengkulu City, Indonesia, and analyzes their administrative and institutional implications. Using a qualitative case study design, data were collected through in-depth interviews with six key informants representing managerial, operational, and citizen perspectives, complemented by policy document analysis and limited observation. The findings reveal that digitalization has contributed to improved procedural efficiency, reduced processing time, and enhanced service accessibility through online monitoring mechanisms. Nevertheless, implementation remains uneven due to infrastructural instability, disparities in digital literacy, and initial organizational resistance to procedural change. Rather than producing an immediate structural transformation, digital reform in this context reflects incremental institutional adaptation shaped by leadership mediation and resource constraints. The study identifies leadership commitment, human resource capacity, inter-unit coordination, and system integration as critical determinants of implementation effectiveness. By situating local administrative realities within broader national digital reform mandates, this research contributes to the growing scholarship on digital governance in emerging economies and offers policy insights for secondary cities pursuing sustainable e-government development.